2016
DOI: 10.12968/bjcn.2016.21.3.148
|View full text |Cite
|
Sign up to set email alerts
|

Community- and hospital-based nurses’ implementation of evidence-based practice: are there any differences?

Abstract: The aim of this paper is to discuss the effect of nurses' beliefs, knowledge, and skills on the implementation of evidence-based practice (EBP) in hospital and community settings. EBP refers to the implementation of the most up-to-date robust research into clinical practice. Barriers have been well documented and traditionally include the negative beliefs of nurses as well as a lack of time, knowledge, and skills. However, with degree entry nursing and a focus on community health care provision, what has chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 36 publications
4
37
1
8
Order By: Relevance
“…Nurses visiting patients in their own home appreciated the time in the car between patients and described it as a productive time to support student nurses. However, nurses working in community hospital settings found that time was a barrier to mentoring student nurses because of competing commitments and finding the time to complete the student nurses practice assessment documentation, which is consistent with previous studies …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nurses visiting patients in their own home appreciated the time in the car between patients and described it as a productive time to support student nurses. However, nurses working in community hospital settings found that time was a barrier to mentoring student nurses because of competing commitments and finding the time to complete the student nurses practice assessment documentation, which is consistent with previous studies …”
Section: Discussionsupporting
confidence: 89%
“…Time as a barrier for nurses to implement EBP has been reported widely and recently . The emergence of time as a facilitator to mentor student nurses during community placements is unique to this study.…”
Section: Discussionmentioning
confidence: 94%
“…A review of the literature revealed that nurses from different countries and settings have consistently complained of experiencing similar barriers to the adoption of EBP, which include lack of time , perception of insufficient power to adjust patient care processes, inadequate organisational support, insufficient access to research journals and articles and insufficient knowledge and skills (Baird & Miller, ; Carroll et al., ; Funk et al., ; Gerrish & Cooke, ; Jordan, Bowers, & Morton, ; Kin et al., ; Mallion & Brooke, ; Mehrdad et al., ; Underhill, Roper, Siefert, Boucher, & Berry, ). In one study, Funk et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these findings should no longer be relevant, given the recent international changes in nurse education (Mallion and Brooke, 2016). Johnson et al (2010) concurred with these findings, and stated that currently nursing education includes research modules to support nurses in evaluating evidence.…”
Section: Evidence-based Practice and The Role Of Researchmentioning
confidence: 99%